2021
DOI: 10.1186/s12903-021-01931-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 45S5 bioactive glass on the remineralization of early carious lesions in deciduous teeth: an in vitro study

Abstract: Background Early childhood caries has been designated as a serious public health problem. The traditional restoration method is very challenging, especially in uncooperative patients. Non-invasive therapy, like remineralization agents, which have been developed to reverse the demineralization progress at the early stage of caries, may be a better choice. This study aimed to evaluate the remineralization efficacy of different concentrations of 45S5 bioactive glass (BAG) on artifical carious lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, this requires glasses with an appropriate particle size. The in vitro study on deciduous teeth by Zhang et al (2021), where 45S5 bioactive glass showed pronounced mineral gain and surface density in remineralizing early carious lesions, exemplifies this requirement [38].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…However, this requires glasses with an appropriate particle size. The in vitro study on deciduous teeth by Zhang et al (2021), where 45S5 bioactive glass showed pronounced mineral gain and surface density in remineralizing early carious lesions, exemplifies this requirement [38].…”
Section: Discussionmentioning
confidence: 80%
“…In aqueous solutions, cations and anions from electrolytes, like those in hydrolyzed bioactive glasses, can bind to oxygen and hydrogen atoms in solvent molecules and to the free -OH groups of the glucose unit of the polysaccharide, forming ionic complexes. Zhang et al (2021) provided a quantitative analysis in their study, showing that the inclusion of 45S5 bioactive glass at concentrations up to 6% could lead to substantial changes in gel viscosity, which in turn influences the gel's ability to facilitate dental remineralization through enhanced ion release and surface interaction [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agar diffusion test can be used when the quality of the antibacterial agents cannot be evaluated with chemical methods, as it depends on the direct proportional relationship between the inhibition zone of the tested microorganisms and the concentration (dose) of the studied agent placed on the agar microbial medium [ 27 , 28 ]. However, it is appropriate only for diffusive materials to determine their antibacterial activity, and the main limitation of this test is the inability to locate whether the material is bactericidal or bacteriostatic, and may affect its reliability in determining some dental toothpaste antibacterial characteristics [ 29 ].…”
Section: Discussionmentioning
confidence: 99%